INTEGRATION OF GEOPARK LOCAL CONTENT IN SOCIAL STUDIES LEARNING: A QUALITATIVE STUDY OF STRENGTHENING LOCAL IDENTITY AND ENVIRONMENTAL AWARENESS AT SMP NEGERI 1 CISOLOK - Andi Priyatna; Sudrajat Sudrajat; Raras Gistha Rosardi (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study aims to analyze the integration of geopark-based local content in social studies learning and its implications for strengthening students' local identity and environmental awareness. The study employs a qualitative approach with a case study design conducted at SMP Negeri 1 Cisolok. The research subjects include social studies teachers, eighth-grade students, and school stakeholders selected purposively. Data collection techniques consist of semi-structured interviews, participatory observation, Likert-scale questionnaires, and documentation. Data analysis applies the interactive model of Miles, Huberman, and Saldaña as well as thematic analysis.The findings reveal three main results. First, geopark-based learning improves students' understanding as the material is connected to real-life experiences in their surrounding environment. Second, the learning process encourages active student engagement through observation activities and contextual discussions. Third, there is a strengthening of local identity and environmental awareness, reflected in students' environmental care attitudes and pride in their region.These findings indicate that geopark integration is effective in creating contextual, meaningful, and character-oriented social studies learning. Theoretically, this study reinforces constructivist approaches and place-based learning. Practically, the results can serve as a reference for teachers and schools in developing environment-based learning. Future research is recommended to test the effectiveness of this model quantitatively and in broader contexts.